Evolution of Blood Safety in Switzerland over the Last 25 Years for HIV, HCV, HBV and Treponema pallidum - Niederhauser, Christoph; Tinguely, Caroline; Stolz, Martin; Vock, Michael; El Dusouqui, Soraya Amar; Gowland, Peter (Viruses, 2022)
During the last few decades, efforts to increase the safety of blood and blood products have mainly focused on preventing the viral infections HCV, HIV, HBV and Treponema pallidum. The evolution of these approaches and the achieved increase in safety is shown for the last 25 years in Switzerland. In detail, the prevalences and incidences of the infection disease and the theoretical estimated residual risks (RR) of these blood-borne infections are presented. Prevalences, incidences and, in particular, the RR have decreased considerably over the last 25 years. This was achieved primarily by the adoption of strict criteria for the selection of blood donors, refined questionnaires, the introduction of increasingly sensitive serological screening tests and the implementation of nucleic acid testing (NAT) for these blood-borne pathogens. These NAT assays have significantly shortened the window period between infection and the first detection of the infectious agent in the blood of an infected individual. A form of “real life” comparison or confirmation is provided by the reported lookback procedures (LBP) and the haemovigilance data of the Swiss competent authority, Swissmedic. These data are in agreement, and thus support the very low prevalences, incidences and RR.